High prevalence of jumper's knee and sonographic changes in Swedish elite junior volleyball players compared to matched controls. Issue 5 (22nd April 2005) - Gisslèn, K; Gyulai, C; Söderman, K; Alfredson, H
Abstract : Background: Jumper's knee is a common and troublesome condition among senior volleyball players, but its prevalence among elite junior players compared to matched non-sports active controls is not known. Objective: To clinically, and by sonography, examine the patellar tendons in elite junior volleyball players (15–19 years) at the Swedish National Centre for volleyball and in matched controls. Methods: The patellar tendons in the 57 students at the Swedish National Centre for high school volleyball and in 55 age, height, and weight matched not regularly sports active controls were evaluated clinically and by grey scale ultrasonography (US) and power Doppler (PD) sonography. Results: There were no significant differences in mean age, height, and weight between the volleyball players and the controls. In the volleyball group, jumper's knee was diagnosed clinically and by US in 12 patellar tendons (10 male and two female). In 12/12 tendons, PD sonography demonstrated a neovascularisation in the area with structural tendon changes. In another 10 pain free tendons, there were structural tendon changes and neovessels. In the control group, no individual had a clinical diagnosis of jumper's knee. US demonstrated structural tendon changes in 11 tendons, but there was no neovascularisation on PD sonography. Conclusions: A clinical diagnosis of jumper's knee, together with structural tendon changes and neovascularisation visualised with sonography, was seen among Swedish elite junior volleyball players but not in matched not regularly sports active controls. Structural tendon change alone was seen in 10% of the control tendons.